Mutation sexuelle, mutation de langage - Alexandre Taalba (Glad!)
Through the story of a young woman whose right big toe changed into a penis, Matsuura Rieko proposes a conception of love and sexuality in terms of gender rather than sex. While the heroine conceived sexuality, by her own admission, exclusively as a heterosexual intercourse, the appearance of her “Big Toe P” makes her face sexuality from the angle of a love relation between two persons, beyond their sex determinations, because the sexual intercourse itself doesn’t demand the genital organ as a priority. When she has to appear on stage with the actors of a theater company where each member has a sex-related distinctive characteristic, she understands that what she is showing, “the penis-vagina union”, is what society establishes as normal sexual intercourse. At the end of her initiatory journey, Kazumi breaks the actor’s paradox in which she has been trapped : what she feels at the beginning of the plot when she thought that she could materialize her love through conventional sexual intercourse and the feeling of frustration while she has to enact this kind of sexual intercourse on scene at the end of the story come into conflict. Apprenticeship of Big Toe P is a Bildungsroman based on a gender study.